PEMEDIASIAN ANTARA PENGARUH E-WOM TERHADAP REPURCHASE INTENTION DENGAN MEDIASI BRAND IMAGE PADA PRODUK SKINCARE MEREK LOKAL INDONESIA YANG ADA DI E-COMMERCE - Putri, Meilisa Regina; Sienarta, Krismi Budi (Ma Chung Press, 2023)
The beauty industry in Indonesia has experienced rapid growth since early 2020 due to high public demand for beauty products. Skincare products with local brands have sprung up a lot. These local skincare product brands are competing to build a positive image through social media so that positive reviews emerge from users of these skincare products. It is hoped that positive reviews from various e-commerce channels will generate repeated buying interest. The purpose of this study was to examine the effect of Electronic Word-of-Mouth (E-WOM) on purchase intentions and its impact on the brand image of Indonesian local skincare products. By examining the relationship between E-WOM and purchase intention, this study aims to find out how online recommendations and discussions influence consumer tendencies to buy products. This research was conducted using a quantitative research approach. The population in this study are all people who use e-commerce applications such as Shopee or Tokopedia to buy products. A total of 90 respondents were taken as samples for this study. The sampling technique used was non-probability purposive sampling, in which respondents were selected purposively based on certain criteria relevant to the study. Data obtained from respondents were then analyzed using the Partial Least Square (PLS) technique. The results of this study indicate that brand image has a significant influence on purchase intention. Consumer reviews on the internet play an important role in shaping brand image, although they do not have a significant influence on consumer purchase intentions. Keywords: E-WOM, Repurchase Intention, Brand Image